Synthesis and EPR studies of soluble vanadyl octakis(4-tert-butylbenzylthio) porphyrazine - Keskin, Bahadir; Yerli, Yusuf; Avciata, Ulvi (TAYLOR & FRANCIS LTD, 2013)
Magnesium porphyrazinate substituted with eight 4-tert-butylphenylthio-groups on peripheral positions has been synthesized by cyclotetramerization of 1,2-bis(4-t-butylphenylthio)maleonitrile in the presence of magnesium butanolate. The metal-free derivative was obtained by treatment with trifluoroacetic acid and further reaction of this product with vanadyl(IV) sulfate led to the vanadyl porphyrazinate. These new compounds have been characterized by elemental analysis, together with FTIR, and UV-vis spectral data. The magnetic properties of the complex have been investigated by electron paramagnetic resonance spectroscopy.
Keywords: Porphyrazine; Vanadyl(IV) sulfate; EPR; SINGLE-CRYSTALS; OPTICAL-PROPERTIES; METAL-COMPLEXES; PHTHALOCYANINES; VO2+; SUBSTITUENTS; CHEMISTRY; LIGANDS; SYSTEM; NI(II)